GOOD CORPORATE GOVERNANCE ARRANGEMENTS IN STATE-OWNED PALM COMPANIES PRIVATE COMPANIES IN INDONESIA - Junaedi , Junaedi (Bajang Institute, 2024)
The concept of GCG has long been known in developed countries, such as Europe and America, with the separation between capital owners and company managers. This concept became hot in America in the eighties when takeover scandals and share sale scandals to management buyouts emerged which worried shareholders. In this case, the company management who was mandated by shareholders did not manage the company well. There is abuse of authority by management for personal interests without considering the interests of shareholders.